Case manager perceptions of emergency department use by patients with non‐fatal suicidal behaviour. (6th November 2020) - Baker, Debra; Blyth, Deborah; Stedman, Terry; Meehan, Tom
Abstract: Repeat presentations to the emergency department (ED) for non‐fatal suicidal behaviour (NFSB) are common in Australia and overseas. The challenges faced by mental health services in managing this sub‐group of patients have not been fully explored. In this qualitative study, we consider how case managers view frequent ED use by patients with NFSB. Individual interviews with case managers were audio‐recorded, transcribed verbatim, and subjected to thematic analysis. Four main themes emerged: a logical place to go; not a lot of benefit from an ED visit; focus on managing risk; and building a life outside of the ED. The case managers noted that patients with NFSB tend to have complex presentations that are challenging to address in the ED. The focus tends to be on assessment of risk with referral to community support agencies. The findings point to the need to identify more intensive care options that support patients to reduce their dependency on the ED. Insights gleaned from the study have implications for those working with NFSB patients.